Progress of photoacoustic imaging combined with targeted photoacoustic contrast agents in tumor molecular imaging - Zheng, Yiwen; Liu, Mengyao; Jiang, Lixin (Frontiers in Chemistry, 2022)
Molecular imaging visualizes, characterizes, and measures biological processes at the molecular and cellular level. In oncology, molecular imaging is an important technology to guide integrated and precise diagnosis and treatment. Photoacoustic imaging is mainly divided into three categories: photoacoustic microscopy, photoacoustic tomography and photoacoustic endoscopy. Different from traditional imaging technology, which uses the physical properties of tissues to detect and identify diseases, photoacoustic imaging uses the photoacoustic effect to obtain the internal information of tissues. During imaging, lasers excite either endogenous or exogenous photoacoustic contrast agents, which then send out ultrasonic waves. Currently, photoacoustic imaging in conjunction with targeted photoacoustic contrast agents is frequently employed in the research of tumor molecular imaging. In this study, we will examine the latest advancements in photoacoustic imaging technology and targeted photoacoustic contrast agents, as well as the developments in tumor molecular imaging research.